Influence of winding topologies and encapsulation materials on FSPM machine thermal performance. Issue 9 (17th June 2020) - Liu, Mingda; Sixel, William; Sarlioglu, Bulent; Nellis, Gregory
Abstract : This study investigates the thermal impact of using different winding topologies and different winding encapsulation materials on dual‐stator 6/4 flux‐switching permanent magnet (FSPM) machine with water jacket cooling. The thermal performance of four different design cases are compared using lumped‐parameter thermal network models. The modelling of the heat transfer in the stator slot, machine air gap and water jacket channel are presented. It is shown that FSPM machines with circumferential winding and toroidal winding have different thermal limiting components and the winding encapsulation material has a different impact on the thermal performance of the two winding topologies. Prototype motors are built and tested to validate the thermal models.